Prevalence of Depression Among Empty-Nest Elderly in China: A Meta-Analysis of Observational Studies - Zhang, Hong-He; Jiang, Yuan-Yuan; Rao, Wen-Wang; Zhang, Qing-E; Qin, Ming-Zhao; Ng, Chee H.; Ungvari, Gabor S.; Xiang, Yu-Tao (Frontiers in Psychiatry, 2020)
Background: Depressive symptoms are common in empty-nest elderly in China, but the reported prevalence rates across studies are mixed. This is a meta-analysis of the pooled prevalence of depressive symptoms (depression hereafter) in empty-nest elderly in China. Methods: Two investigators independently conducted a systematic literature search in both English (PubMed, EMBASE, PsycINFO, Web of Science and Cochrane Library) and Chinese (CNKI and Wan Fang) databases. Data were analyzed using the Comprehensive Meta-Analysis program. Results: A total of 46 studies with 36,791 subjects were included. The pooled prevalence of depression was 38.6% (95%CI: 31.5%-46.3%). Compared with non-empty-nest elderly, empty-nest elderly were more likely to suffer from depression (OR=2.0, 95%CI: 1.4 to 2.8, P<0.001). Subgroup and meta-regression analyses revealed that mild depressive symptoms were more common in empty-nest elderly than moderate or severe depressive symptoms (P<0.001). In addition, living alone, higher male proportion, later year of publication and higher study quality score were significantly associated with higher prevalence of depressive symptoms (all P values<0.05). Conclusion: In this meta-analysis, the prevalence of depressive symptoms in empty-nest elderly was high in China. Considering the negative impact of depression on health outcomes and well-being, regular screening and appropriate interventions need to be delivered for this vulnerable segment of the population.